High-inductance copper-iron co-fired inductor and preparation method thereof

Through the introduction of nano -crystal band materials and gas atomized iron nickel -molybdenum powder and other materials in copper -iron co -inductance, the problem of low existing inductance and inductance value is solved, and the effect of high induction value, low loss and high reliability is achieved.

CN119381113AActive Publication Date: 2025-01-28HEFEI MAIWEI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411516908.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The inductance value of existing copper-iron co-fired inductors is low, making it difficult to meet the needs of high efficiency, high power density and miniaturization of electronic products.

Method used

By introducing nano -crystal band materials in copper conductor and soft magnetic metal powder, and combined with different particle size, air -five iron nickel nickel molybdenum powder, passivation agent, covering agent and lubricant, high -density, high magnetic guidance rate Unempathic materials.

Benefits of technology

It significantly improves the inductance value, improves the strength and stability of the inductance, while reducing the loss of loss, and improving the reliability of the inductance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381113A_ABST
    Figure CN119381113A_ABST
Patent Text Reader

Abstract

The invention provides a high-inductance copper-iron co-fired inductor which comprises soft magnetic metal powder, a copper conductor and a nanocrystalline strip, the copper conductor and the nanocrystalline strip are vertically connected and buried in the soft magnetic metal powder, and the two ends of the copper conductor extend out of the soft magnetic metal powder; the soft magnetic metal powder comprises mixed powder of gas atomized iron-nickel-molybdenum powder with different particle sizes, a passivating agent, a coating agent and a lubricating agent. The passivating agent is a mixed solution of oxalic acid and nitric acid; the coating agent is an acetone solution of fluorosilicone resin, titanium trifluoride, aluminum trifluoroacetyl pyruvate and nano barium titanate; the lubricant is a mixture of gas-phase aluminum oxide and niobium diselenide; the thickness of the nanocrystalline strip ranges from 1 micrometer to 1.5 micrometers, and the width of the nanocrystalline strip ranges from 2 mm to 4 mm. According to the inductor, the inductance value of the inductor reaches the highest value by utilizing the gas atomization iron-nickel-molybdenum powder with the highest magnetic conductivity in the soft magnetic metal powder, and meanwhile, the gas atomization iron-nickel-molybdenum powder has very low loss and excellent stability, so that the inductor has good loss performance and excellent reliability at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic functional materials, and in particular relates to a high-inductance copper-iron co-fired inductor and a preparation method thereof. Background Art

[0002] Chip inductors are a key component of chip power modules, and they provide power to the front end of chips such as GPUs and CPUs. As electronic products develop towards high efficiency, high power density, and miniaturization, the performance improvement and volume optimization of chip inductors have become urgent issues that need to be addressed.

[0003] The most emerging chip inductor is the copper-iron co-fired inductor. The so-called copper-iron co-fired inductor is a process that combines magnetic powder core and one-piece molded inductor. The copper wire or copper sheet buried inside the soft magnetic metal powder is pressed and molded using high pressure. This can not only achieve the high density and high magnetic permeability characteristics of the magnetic powder core material, but also achieve the "iron-clad copper" magnetic shielding and mechanized mass production advantages of the one-piece molded inductor. However, due to the immaturity of copper-iron co-fired inductor technology, the inductor performance still needs to be improved. The most obvious disadvantage is the low inductance value of copper-iron co-fired inductors, because copper-iron co-fired inductors basically use a single copper conductor combined with soft magnetic metal powder, and the inductance value of the inductor device is proportional to the square of the number of turns of the coil and proportional to the first power of the magnetic permeability of the soft magnetic metal powder. Without improving the structure, it is difficult to increase the inductance value of a single turn of copper conductor. Summary of the invention

[0004] The technical problem to be solved by the present invention is how to increase the inductance value of the copper-iron co-fired inductor.

[0005] The present invention solves the above technical problems through the following technical means:

[0006] The first aspect of the present invention provides a high-inductance copper-iron co-fired inductor, comprising soft magnetic metal powder, a copper conductor and a nanocrystalline strip, wherein the copper conductor is vertically connected to the nanocrystalline strip and buried in the soft magnetic metal powder, and both ends of the copper conductor extend out of the soft magnetic metal powder; the soft magnetic metal powder comprises a mixed powder of atomized iron-nickel-molybdenum powders of different particle sizes, a passivator, a coating agent and a lubricant; the passivator is a mixed solution of oxalic acid and nitric acid; the coating agent is an acetone solution of fluorosilicone resin, titanium trifluoride, aluminum trifluoroacetylacetonate and nano-barium titanate; the lubricant is a mixture of gas-phase aluminum oxide and niobium diselenide; the thickness of the nanocrystalline strip is 1-1.5um and the width is 2-4mm.

[0007] Beneficial effect: The present invention utilizes atomized iron-nickel-molybdenum powder with the highest magnetic permeability among soft magnetic metal powders to achieve the highest inductance value of the inductor. At the same time, the atomized iron-nickel-molybdenum powder has very low loss and excellent stability. Therefore, the inductor has both good loss performance and excellent reliability.

[0008] The present invention forms a basic framework by connecting nanocrystalline ribbons and copper conductors. The nanocrystalline ribbons play a role of stable support in the inductor, greatly improving the strength of the inductor product. The nanocrystalline ribbons have a magnetic permeability much higher than that of soft magnetic metal powders and a loss much lower than that of soft magnetic metal powders, which significantly increases the inductance value of the inductor.

[0009] The lubricant used in the present invention is a mixture of fumed aluminum oxide and niobium diselenide. After the fumed aluminum oxide is mixed with the atomized iron-nickel-molybdenum powder, it can be orderly combined on the surface of the powder particles to form a shell layer. This shell layer can effectively reduce the electrostatic attraction between the particles and avoid powder adhesion caused by van der Waals forces, moisture absorption, particle friction, etc., thereby improving the fluidity of the powder and increasing the inductance value of the inductor.

[0010] Preferably, the different particle sizes are D50=28-35 μm, D50=10-14 μm and D50=3-5 μm, respectively, and the aerosolized iron-nickel-molybdenum powders of different particle sizes account for 60%, 20% and 20% of the mixed powder, respectively.

[0011] More preferably, the different particle sizes are D50=30 μm, D50=12 μm and D50=4.8 μm respectively.

[0012] Beneficial effect: The present invention utilizes aerosolized iron-nickel-molybdenum powders of three particle sizes, namely, coarse, medium and fine, to mix, so that the aerosolized iron-nickel-molybdenum mixed powder has better sphericity, and increases the dense contact between the powder particles. The aerosolized iron-nickel-molybdenum powder with a mass ratio and a particle size ratio of the present invention can achieve high-density filling of magnetic powder and achieve high inductance performance.

[0013] Preferably, the mass of the oxalic acid accounts for 0.2-0.4% of the mixed powder, and the mass of the nitric acid accounts for 0.05-0.1% of the mixed powder.

[0014] Preferably, the mass of the fluorosilicone resin accounts for 1.0-1.5% of the mixed powder, the mass of the titanium trifluoride accounts for 0.05-0.2% of the mixed powder, the mass of the aluminum trifluoroacetylacetonate accounts for 0.1-0.5% of the mixed powder, the mass of the nano-barium titanate accounts for 0.05-0.15% of the mixed powder, and the mass of acetone accounts for 8-10% of the mixed powder.

[0015] Preferably, the mass of the fumed aluminum oxide accounts for 0.02-0.04% of the mixed powder, and the mass of the niobium diselenide accounts for 0.2-0.4% of the mixed powder.

[0016] The second aspect of the present invention provides a method for preparing the above-mentioned high-inductance copper-iron co-fired inductor, comprising the following steps:

[0017] (1) A soft magnetic metal powder is prepared by a blending method, a nanocrystalline strip is vertically fixed on the surface of a copper conductor, and then placed in the soft magnetic metal powder, with both ends of the copper conductor extending out of the soft magnetic metal powder to obtain a magnetic powder core;

[0018] (2) The magnetic powder core is subjected to bidirectional pressing through a mold, and then subjected to gradient annealing in a reducing atmosphere, and finally immersed in a resin solution, and after washing and baking, a high-inductance copper-iron co-fired inductor is obtained.

[0019] Preferably, the specific operation of blending is to first mix aerosolized iron-nickel-molybdenum powders of different particle sizes, and then sequentially mix them with a passivator, a coating agent and a lubricant to obtain a soft magnetic metal powder.

[0020] Preferably, the gradient annealing includes three stages. In the first stage, the temperature is raised from room temperature to 400-450°C, and the holding time is 30-40 minutes; in the second stage, the temperature is raised to 500-520°C, and the holding time is 30-40 minutes; in the third stage, the temperature is raised to 540-570°C, and the holding time is 30-40 minutes, and finally it is quickly cooled to room temperature.

[0021] Preferably, the pressure of the bidirectional pressing is 1600-2200 MPa; the reducing atmosphere is a mixed gas of hydrogen and argon, wherein the volume of hydrogen accounts for 5-10% of the volume of the mixed gas, and the volume of argon accounts for 90-95% of the volume of the mixed gas.

[0022] Preferably, the immersion is vacuum impregnation, the resin solution is an acetone solution of fluorosilicone resin, the impregnation time is 30-50 minutes, the acetone washing time after impregnation is 0.5-1.0 minutes, and the baking condition is 160-180° C. and kept warm for 60-80 minutes.

[0023] Beneficial effects: Nanocrystalline ribbons have the characteristics of high magnetic permeability and low loss only after annealing, while the soft magnetic properties of nanocrystalline ribbons that have not been heat treated are very poor; after high-pressure pressing of the magnetic powder core, a large amount of stress will remain inside, resulting in low magnetic permeability and high loss. Only through annealing process can the purpose of stress relief and loss reduction be achieved.

[0024] The present invention uses gradient annealing in a reducing atmosphere to make the nanocrystalline crystallization curve and the stress relief annealing curve coincide with each other, which can not only complete the nanocrystalline crystallization of the nanocrystalline strip, but also eliminate the internal stress of the iron-nickel-molybdenum powder after being pressed into an inductor, thereby improving the inductance value of the inductor.

[0025] The present invention uses a mixed solution of oxalic acid and nitric acid as a passivating agent, wherein nitric acid provides acidity and oxidizing properties, promoting the passivation reaction of oxalic acid and atomized iron-nickel-molybdenum powder, and the generated iron oxalate will decompose into iron oxide during high-temperature annealing, so that it can be evenly coated on the surface of the powder, improve the insulation performance of the powder, reduce the eddy current loss between powders, and thus reduce the total loss of the inductor. Similarly, the added aluminum trifluoroacetylacetonate will also decompose into aluminum oxide during high-temperature annealing, and grow evenly on the surface of the powder, effectively reducing the inductor loss.

[0026] Titanium trifluoride is used in the coating agent of the present invention. Titanium trifluoride has very good insulation and thermal stability. It will not decompose due to heat during high-temperature annealing, ensuring the stability of the coating layer. More importantly, titanium trifluoride has a certain negative thermal expansion coefficient, that is, it will not expand in volume due to heat during high-temperature annealing, but will shrink in volume due to heat. This can better avoid the problem of film rupture caused by the expansion of the coating, ensuring the integrity of the film. Niobium diselenide is used in the lubricant of the present invention. Niobium diselenide is rapidly transformed into a liquid lubricating film due to the sharp increase in pressure and temperature during the bidirectional pressing process of the magnetic powder core, playing a lubricating role. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure of a high-inductance copper-iron co-fired inductor in an embodiment;

[0028] Figure 2 Schematic diagram of the arrangement of copper conductor and nanocrystalline strip in the high-inductance copper-iron co-fired inductor in the embodiment;

[0029] In the figure: 1-copper conductor; 2-nanocrystalline strip; 3-soft magnetic metal powder. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0032] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0033] Example 1

[0034] This embodiment provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor; specifically, the following steps are included:

[0035] (1) Preparation of soft magnetic metal powder: 60 g of aerosolized iron-nickel-molybdenum powder with D50=30 μm, 20 g of aerosolized iron-nickel-molybdenum powder with D50=12 μm and 20 g of aerosolized iron-nickel-molybdenum powder with D50=4.8 μm were mixed uniformly; 0.20 g of oxalic acid and 0.05 g of nitric acid and an appropriate amount of distilled water were added to the mixed powder, stirred and heated to 110°C, and the powder was dried and cooled to room temperature; 1.0 g of fluorosilicone resin, 0.05 g of titanium trifluoride, 0.1 g of aluminum trifluoroacetylacetonate, 0.05 g of nano-barium titanate and 10 g of acetone solution were added to the cooled powder, stirred and heated to 50°C, and the powder was dried and cooled to room temperature to obtain coated powder; 0.02 g of fumed alumina and 0.2 g of niobium diselenide were added to the coated powder and mixed uniformly to obtain soft magnetic metal powder.

[0036] (2) Preparation of magnetic powder core: A nanocrystalline strip with a thickness of 1.0 μm and a width of 2.0 mm is vertically attached to the surface of a copper conductor. Figure 2 As shown, it is then placed in soft magnetic metal powder, with both ends of the copper conductor extending out of the soft magnetic metal powder to obtain a magnetic powder core.

[0037] (3) placing the magnetic powder core in a mold and performing bidirectional pressing at 1800 MPa to obtain a pressed product; performing gradient annealing on the pressed product in a mixed gas of hydrogen and argon, wherein the volume of hydrogen accounts for 10% of the volume of the mixed gas, and the volume of argon accounts for 90% of the volume of the mixed gas, and the specific operation of the gradient annealing is to heat from room temperature to 400°C, keep the temperature for 30 minutes, then heat to 500°C and keep the temperature for 35 minutes, then heat to 540°C and keep the temperature for 30 minutes, and finally quickly cool to room temperature; vacuum impregnating the annealed product in a fluorosilicone resin solution for 40 minutes, then washing with acetone for 1 minute, and baking at 180°C for 70 minutes to obtain a high-inductance copper-iron co-fired inductor, such as Figure 1 shown.

[0038] The high-inductance copper-iron co-fired inductor prepared in this embodiment was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0039] Example 2

[0040] This embodiment provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor; specifically, the following steps are included:

[0041] (1) Preparation of soft magnetic metal powder: 60 g of aerosolized iron-nickel-molybdenum powder with D50=30 μm, 20 g of aerosolized iron-nickel-molybdenum powder with D50=12 μm and 20 g of aerosolized iron-nickel-molybdenum powder with D50=4.8 μm were mixed uniformly; 0.3 g of oxalic acid and 0.1 g of nitric acid and an appropriate amount of distilled water were added to the mixed powder, stirred and heated to 110°C, and the powder was dried and cooled to room temperature; 1.5 g of fluorosilicone resin, 0.12 g of titanium trifluoride, 0.30 g of aluminum trifluoroacetylacetonate, 0.15 g of nano-barium titanate and 10 g of acetone solution were added to the cooled powder, stirred and heated to 50°C, and the powder was dried and cooled to room temperature to obtain coated powder; 0.04 g of fumed alumina and 0.3 g of niobium diselenide were added to the coated powder and mixed uniformly to obtain soft magnetic metal powder.

[0042] (2) Preparation of magnetic powder core: A nanocrystalline strip with a thickness of 1.5 μm and a width of 3.0 mm is vertically attached to the surface of a copper conductor. Figure 2 As shown, it is then placed in soft magnetic metal powder, with both ends of the copper conductor extending out of the soft magnetic metal powder to obtain a magnetic powder core.

[0043] (3) placing the magnetic powder core in a mold and performing bidirectional pressing at 2000 MPa to obtain a pressed product; performing gradient annealing on the pressed product in a mixed gas of hydrogen and argon, wherein the volume of hydrogen accounts for 5% of the volume of the mixed gas, and the volume of argon accounts for 95% of the volume of the mixed gas, and the specific operation of the gradient annealing is to heat the product from room temperature to 420°C, keep the temperature for 40 minutes, then heat the product to 510°C and keep the temperature for 35 minutes, then heat the product to 570°C and keep the temperature for 30 minutes, and finally quickly cool the product to room temperature; vacuum impregnating the annealed product in a fluorosilicone resin solution for 40 minutes, then washing with acetone for 0.5 minutes, and baking at 160°C for 60 minutes to obtain a high-inductance copper-iron co-fired inductor, such as Figure 1 shown.

[0044] The high-inductance copper-iron co-fired inductor prepared in this embodiment was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0045] Comparative Example 1

[0046] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that the mixed powder used in step (1) is 100g of atomized iron-nickel powder with D50=30μm.

[0047] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0048] Comparative Example 2

[0049] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that the mixed powder used in step (1) is 60g of atomized sendustine-silicon-aluminum powder with D50=30μm and 40g of atomized iron silicon powder with D50=12μm.

[0050] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0051] Comparative Example 3

[0052] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that the passivating agent used in step (1) is 0.25 g of phosphoric acid.

[0053] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0054] Comparative Example 4

[0055] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that the coating agent used in step (1) is 1.20 g of epoxy resin.

[0056] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0057] Comparative Example 5

[0058] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that the lubricant used in step (1) is 0.22 g of magnesium stearate.

[0059] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0060] Comparative Example 6

[0061] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that step (2) does not use nanocrystalline strips.

[0062] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0063] Comparative Example 7

[0064] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that a pure nitrogen atmosphere is used in step (3) gradient annealing.

[0065] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0066] Comparative Example 8

[0067] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 1 is that no gradient heating is used in the annealing process of step (3). Specifically, the temperature is raised from room temperature to 540° C. and kept for 30 minutes, and then cooled to room temperature in the furnace.

[0068] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0069] Comparative Example 9

[0070] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 2 is that the mixed powder used in step (1) is 60g of D50=30μm, 20g of D50=12μm, and 20g of water-atomized iron-silicon-chromium powder with D50=4.8μm.

[0071] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0072] Comparative Example 10

[0073] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 2 is that the mixed powder used in step (1) is 100g of carbonyl iron powder, and D50=12μm.

[0074] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0075] Comparative Example 11

[0076] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 2 is that in step (1), 0.4 g of nitric acid is added after the mixed powder is passivated.

[0077] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0078] Comparative Example 12

[0079] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 2 is that the coating agent used in step (1) is 2.07 g of acetone solution of fluorosilicone resin.

[0080] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0081] Comparative Example 13

[0082] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 2 is that step (2) uses an amorphous strip with a thickness of 1.5 um and a width of 3.0 mm.

[0083] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0084] Comparative Example 14

[0085] This comparative example provides a method for preparing a high-inductance copper-iron co-fired inductor and the obtained inductor. The difference between this comparative example and Example 2 is that step (2) uses a nanocrystalline strip with a thickness of 2.5um and a width of 5.5mm.

[0086] The high-inductance copper-iron co-fired inductor prepared in this comparative example was subjected to characteristic tests. The characteristic test results are shown in Table 1.

[0087] Experimental example

[0088] The high-inductance copper-iron co-fired inductors prepared in Examples 1-2 and Comparative Examples 1-14 were tested for inductance and power loss performance. In this experimental example, the inductance was tested using a WK6500B precision impedance analyzer and the loss was tested using an Iwasaki SY8218BH analyzer. The results of the characteristic tests are shown in Table 1 below.

[0089] Table 1: Property test results of Examples 1-2 and Comparative Examples 1-14

[0090]

[0091] According to Table 1, compared with Comparative Examples 1-8, Example 1 uses a mixture of three types of gas-atomized iron-nickel-molybdenum powders of different particle sizes, passivated and coated in the present invention, and combined with the addition of nanocrystalline narrow bands, a copper-iron co-fired inductor with high inductance can be obtained while also having relatively low power loss.

[0092] Comparison of Comparative Examples 1 and 2 with Example 1 shows that the aerosolized iron-nickel-molybdenum powder has obvious advantages in high magnetic permeability and low loss after the particle size is matched. Comparison of Comparative Examples 3, 4, and 5 with Example 1 proves that the passivation and coating of the aerosolized iron-nickel-molybdenum mixed powder have significant effects on magnetic permeability and loss, and the change of materials brings about changes in performance. Comparison of Comparative Example 6 with Example 1 shows that the nanocrystalline narrow band has a significant effect on improving inductance, because the magnetic permeability of the nanocrystalline narrow band can reach 20000-80000 after nanocrystallization, which is much higher than the common 19-160 magnetic permeability of the powder core material. In addition, the nanocrystalline narrow band can improve the stability of the inductance and reduce power loss.

[0093] Comparative Example 7 is compared with Example 1. In the annealing process, pure nitrogen is used in Comparative Example 7. Since it has no reducing property, it cannot reduce the oxidation problem caused by high temperature during the powder making process, so the problem of low inductance and high loss occurs. Comparative Example 8 is compared with Example 1, which shows that a suitable temperature curve can achieve nanocrystallization and eliminate internal stress of nanocrystalline ribbons, but too fast a heating rate makes it difficult to achieve nanocrystallization and eliminate internal stress, resulting in increased power loss.

[0094] Compared with Example 2, Comparative Examples 9 and 10 have obvious advantages in high magnetic permeability and low loss of the gas-atomized iron-nickel-molybdenum mixed powder after the particle size matching. Comparative Examples 11 and 12 are compared with Example 2, which proves that the passivation and coating of the gas-atomized iron-nickel-molybdenum mixed powder have significant effects on magnetic permeability and loss, and the change of materials brings about the change of performance. Comparative Example 13 is compared with Example 2, which shows that the nanocrystalline narrow band has a significant effect on improving inductance, and other materials cannot improve inductance.

[0095] Comparison of Comparative Example 14 with Example 2 shows that only the nanocrystalline narrow strips have a significant effect on improving inductance, because the gaps between the nanocrystalline narrow strips are large, and the bonding by atomized iron-nickel-molybdenum mixed powder has good bonding strength, so the prepared inductor is not easy to crack. When the width and thickness of the nanocrystalline strips are large, the gaps between the nanocrystalline strips are small, and the bonding strength of the atomized iron-nickel-molybdenum mixed powder is small, so the prepared inductor is easy to crack, resulting in reduced inductance and increased power loss, and the inductor cannot be used.

[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-inductance copper-iron co-fired inductor, characterized in that: It comprises soft magnetic metal powder, copper conductor and nanocrystalline strip, wherein the copper conductor is vertically connected with the nanocrystalline strip and buried in the soft magnetic metal powder, and both ends of the copper conductor extend out of the soft magnetic metal powder; The soft magnetic metal powder comprises a mixed powder of atomized iron, nickel and molybdenum powders of different particle sizes, a passivator, a coating agent and a lubricant; the passivator is a mixed solution of oxalic acid and nitric acid; the coating agent is an acetone solution of fluorosilicone resin, titanium trifluoride, aluminum trifluoroacetylacetonate and nano-barium titanate; the lubricant is a mixture of fumed aluminum oxide and niobium diselenide; The nanocrystalline ribbon has a thickness of 1-1.5 um and a width of 2-4 mm.

2. The high inductance copper-iron co-fired inductor according to claim 1 is characterized in that: The different particle sizes are D50=28-35 μm, D50=10-14 μm and D50=3-5 μm, respectively. The atomized iron-nickel-molybdenum powders with different particle sizes account for 60%, 20% and 20% of the mixed powder respectively.

3. The high inductance copper-iron co-fired inductor according to claim 1, characterized in that: The mass of the oxalic acid accounts for 0.2-0.4% of the mixed powder, and the mass of the nitric acid accounts for 0.05-0.1% of the mixed powder.

4. The high inductance copper-iron co-fired inductor according to claim 1, characterized in that: The mass of the fluorosilicone resin accounts for 1.0-1.5% of the mixed powder, the mass of the titanium trifluoride accounts for 0.05-0.20% of the mixed powder, the mass of the aluminum trifluoroacetylacetonate accounts for 0.1-0.5% of the mixed powder, the mass of the nano-barium titanate accounts for 0.05-0.15% of the mixed powder, and the mass of acetone accounts for 8-10% of the mixed powder.

5. The high inductance copper-iron co-fired inductor according to claim 1, characterized in that: The mass of the gas phase aluminum oxide accounts for 0.02-0.04% of the mixed powder, and the mass of the niobium diselenide accounts for 0.2-0.4% of the mixed powder.

6. The method for preparing a high-inductance copper-iron co-fired inductor according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) A soft magnetic metal powder is prepared by a blending method, a nanocrystalline strip is vertically fixed on the surface of a copper conductor, and then placed in the soft magnetic metal powder, with both ends of the copper conductor extending out of the soft magnetic metal powder to obtain a magnetic powder core; (2) The magnetic powder core is subjected to bidirectional pressing through a mold, and then subjected to gradient annealing in a reducing atmosphere, and finally immersed in a resin solution, and after washing and baking, a high-inductance copper-iron co-fired inductor is obtained.

7. The method for preparing a high-inductance copper-iron co-fired inductor according to claim 6, characterized in that: The specific operation of the blending is to first mix atomized iron-nickel-molybdenum powders of different particle sizes, and then sequentially mix them with a passivator, a coating agent and a lubricant to obtain a soft magnetic metal powder.

8. The method for preparing a high-inductance copper-iron co-fired inductor according to claim 6, characterized in that: The gradient annealing includes three stages. In the first stage, the temperature is raised from room temperature to 400-450°C for 30-40 minutes; in the second stage, the temperature is raised to 500-520°C for 30-40 minutes; in the third stage, the temperature is raised to 540-570°C for 30-40 minutes, and finally the material is rapidly cooled to room temperature.

9. The method for preparing a high-inductance copper-iron co-fired inductor according to claim 6, characterized in that: The pressure of the bidirectional pressing is 1600-2200Mpa; the reducing atmosphere is a mixed gas of hydrogen and argon, wherein the volume of hydrogen accounts for 5-10% of the volume of the mixed gas, and the volume of argon accounts for 90-95% of the volume of the mixed gas.

10. The method for preparing a high-inductance copper-iron co-fired inductor according to claim 6, characterized in that: The impregnation is vacuum impregnation, the resin solution is an acetone solution of fluorosilicone resin, the impregnation time is 30-50 minutes, the acetone washing time after impregnation is 0.5-1.0 minutes, and the baking condition is to keep warm at 160-180° C. for 60-80 minutes.

Citation Information

Patent Citations

  • Direct insertion type integrally-formed co-fired inductor and preparation method thereof

    CN115938718A

  • ALLOY COMPOSITION, Fe-BASED NANO-CRYSTAL ALLOY RIBBON, Fe-BASED NANO-CRYSTAL ALLOY POWDER AND MAGNETIC PART

    JP2015157999A

  • Manufacturing method of wound magnetic core and wound magnetic core

    JP2020017608A

  • Co-fired ceramic inductors with variable inductance, and voltage regulator having same

    US20070222549A1

  • Method for Manufacturing A Magnet From Recycled Magnets

    US20230317329A1

Cited By

  • Soft magnetic metal powder and preparation method thereof, and copper-iron co-fired inductor and preparation method thereof

    CN120636995A